Mechanistic Study of Photocatalytic Hydrogen Generation with Simple Iron Carbonyls as Water Reduction Catalysts. Issue 2 (3rd November 2015) - Fischer, Steffen; Bokareva, Olga S.; Barsch, Enrico; Bokarev, Sergey I.; Kühn, Oliver; Ludwig, Ralf
Abstract: This study provides new insights into light‐driven hydrogen generation using an iridium photosensitizer (IrPS) and simple iron carbonyls as water reduction catalysts (WRCs). Stopped‐flow rapid‐scan FTIR and operando continuous‐flow FTIR spectroscopy as well as time‐dependent density functional theory (TD‐DFT) has been applied to study the reaction. The conversion of the WRC precursor [Fe3 (CO)12 ] into the radicals [Fe3 (CO)11 ] . − and [Fe2 (CO)8 ] . − as well as [Fe(CO)5 ] in the absence of light in a solvent mixture of tetrahydrofuran, triethylamine, and water has been studied quantitatively. During light‐induced hydrogen production in the presence of the IrPS, the trimeric [HFe3 (CO)11 ] − and the monomeric [HFe(CO)4 ] − anion could be identified as major WRC species. The equilibrium between both species can be shifted completely towards [HFe(CO)4 ] − by increasing the water content of the solvent mixture. Application of other iron(0) carbonyl compounds as WRC precursors also results in the exclusive formation of [HFe(CO)4 ] − . Kinetic experiments show that the stability of the system is primarily influenced by the applied amount of WRC precursor, whereas the reaction rate is mainly determined by the concentration of the IrPS. At least two loss channels could be identified: light‐induced CO dissociation from the WRC and decomposition of the IrPS at high IrPS/WRC ratios, accompanied by a ligand transfer from the iridium towards the iron center of the WRC. To reveal the nature of the catalytically active complex, binding energies and charge‐transfer probabilities of all coordination geometries of various IrPS⋅⋅⋅ WRC complexes have been calculated. These computations indicate an increased probability of charge transfer for dimeric and trimeric iron carbonyl species. Abstract : Mechanisms of water reduction : This mechanistic study provides new detailed insights into homogeneous photocatalytic water reduction using an iridium dye/iron carbonyl system. It shows the system's loss channels and reveals the nature of the catalytically active complex by application of stopped‐flow rapid‐scan and operando continuous‐flow FTIR spectroscopy as well as time‐dependent density functional theory. SR=Sacrificial reductant, IrPS=Iridium photosensitizer, WRC=Water reduction catalyst.